Control Quality of E-Learning Implementation Management - Indah Komsiyah (STAI Hubbulwathan Duri, 2023)
The purpose of this research was to obtain the implementation of control quality management for e-learning. This research was qualitative research through the method of description. The research was conducted at one of the Islamic State Universities in Tulungagung. Participants were lecturers from the Islamic Religious Education study program and the team in charge of higher education quality assurance (n=50). Data collection used documents, observations, and questionnaires. Data analysis techniques used were 1) data reduction, 2) data display, and 3) conclusion/verification. The results of the study concluded that the quality control of e-learning that needs to be considered by the quality assurance team is the quality of learning design, interaction and communication. In terms of content, assessment and evaluation, the human resources and technology systems are of high quality and meet the standards of online learning needs. The results of the research had implications for understanding the concept of implementing different educational quality assurance between e-learning and face-to-face learning.